Thermal Acclimation and Adaptation in Marine Protozooplankton and Mixoplankton - Calbet, Albert; Saiz, Enric (Frontiers in Microbiology, 2022)
Proper thermal adaptation is key to understanding how species respond to long-term changes in temperature. However, this is seldom considered in protozooplankton and mixoplankton experiments. In this work, we studied how two heterotrophic dinoflagellates (Gyrodinium dominans and Oxyrrhis marina), one heterotrophic ciliate (Strombidium arenicola), and one mixotrophic dinoflagellate (Karlodinium armiger) responded to warming. To do so, we compared strains adapted at 16, 19 and 22 °C and those adapted at 16 °C and exposed for 3 days to temperature increases of 3 and 6°C (acclimated treatments). Neither their CNP contents nor their corresponding elemental ratios showed straightforward changes with temperature, except for a modest increase in P contents with temperature in some grazers. In general, the performance of both acclimated and adapted grazers increased from 16 to 19 °C and then dropped at 22 °C, with a few exceptions. Therefore, our organisms followed the “hotter is better” hypothesis for a temperature rise of 3°C; an increase of > 6°C, however, resulted in variable outcomes. Despite the disparity in responses among species and physiological rates, 19 °C-adapted organisms, in general, performed better than acclimated-only (16ºC-adapted organisms incubated at +3ºC). However, at 22 °C, most species were at the limit of their metabolic equilibrium and were unable to fully adapt. Nevertheless, adaptation to higher temperatures allowed strains to maintain physiological activities when exposed to sudden increases in temperature (up to 25 °C). In summary, adaptation to temperature seems to confer a selective advantage to protistan grazers within a narrow range (i.e., ca. 3 °C). Adaptation to much higher increases of temperatures (i.e., +6 °C) does not confer any clear physiological advantage (with few exceptions; e.g., the mixotroph K. armiger), at least within the time frame of our experiments.